Comparison of two field methods for estimating body fat in different Spanish Dance disciplines - José Ramón Alvero-Cruz (Nutrición Hospitalaria, 2014)
The purpose of the present study was to investigate per- centage body fat (%BF) differences in three Spanish dance disciplines and to compare skinfold and bioelectrical impe- dance predictions of body fat percentage in the same sample. Seventy-six female dancers, divided into three groups, Classical (n=23), Spanish (n=29) and Flamenco (n=24), were measured using skinfold measurements at four sites: triceps, subscapular, biceps and iliac crest, and whole body multi-frequency bioelectrical impedance (BIA). The skin- fold measures were used to predict body fat percentage via Durnin and Womersley’s and Segal, Sun and Yannakoulia equations by BIA. Differences in percent fat mass between groups (Classical, Spanish and Flamenco) were tested by using repeated measures analysis (ANOVA). Also, Pear- son’s product-moment correlations were performed on the body fat percentage values obtained using both methods. In addition, Bland-Altman plots were used to assess agree- ment, between anthropometric and BIA methods. Repeated measures analysis of variance did not found differences in %BF between modalities (  <0.05). Fat per- centage correlations ranged from r = 0.57 to r =0.97 (all,  <0.001). Bland-Altman analysis revealed differences be- tween BIA Yannakoulia as a reference method with BIA Segal (-0.35 ± 2.32%, 95%CI: -0.89to 0.18,  =0.38), with BIA Sun (-0.73 ± 2.3%, 95%CI: -1.27 to -0.20,  =0.014) and Durnin-Womersley (-2.65 ± 2,48%, 95%CI: -3.22 to -2.07,  <0.0001). It was concluded that body fat percen- tage estimates by BIA compared with skinfold method were systematically different in young adult female ba- llet dancers, having a tendency to produce underestima- tions as %BF increased with Segal and Durnin-Womers- ley equations compared to Yannakoulia, concluding that these methods are not interchangeable.